Introducing CISCO Unified Computer System : learn Cisco UCS with CISCO UCSPE - Fordham, Stuart (APRESS, 2023)
The Cisco Unified Computing System (UCS) can be found in the majority of data centers across the world. However, getting hands-on practice to learn this infrastructure can be difficult, as many companies will push to have it production-ready as soon as possible. Home-labs are also cost-prohibitive, cumbersome, electricity-hungry, and noisy. So, how do you get hands-on experience? With Unified Computing System Platform Emulator (UCSPE) and this book. UCSPE is free and can run on a laptop. Using it along with this book, you will learn how to set up, manage and troubleshoot a UCS, including the fabric interconnects, chassis and IOMs, and servers through the GUI and the CLI. All from the comfort of your own home. Introducing Cisco Unified Computing System will show you how to set up a UCS (comparing the UCSPE to a real-world deployment), customize the hardware, configure the UCS system, and secure it. You'll start by creating an organization and then the policies to control storage, networking, boot options, maintenance policies, and server pools. Once you have the required policies you'll use them to create service profiles (using the policies) and templates and assign these to the blade and rack-mount servers in the virtual environment. You'll also be looking at real-life scenarios such as upgrades (and downgrades), northbound networking, and Storage Area Networking (SAN) connectivity. Using the GUI and the CLI you'll look at real-world examples that data center engineers may encounter. What You'll Learn Set up the Cisco UCSPE on VMWare Create UCS service profiles Secure the UCS system Troubleshoot the UCS Who This Book Is For Datacenter and network engineers and individuals studying for the CCNA and CCNP Cisco data center qualification.